Differential scanning calorimetry (DSC) studies on the thermal properties of peanut proteins - Colombo, Andrés (2010)
Studies related to the functional and thermal properties of peanut proteins are limited if compared with other vegetable protein sources. The aim of this work was to study the thermal denaturation of peanut protein isolates (PPI) by DSC. The thermal profile of PPI showed two endothermic peaks (assigned to denaturation of arachin and conarachin fractions). The thermal stability of arachin and conarachin increased when water content decreased, and a critical water level was found for both fractions. The effect of protein denaturants was studied. Low contents of urea stabilized protein fractions, but lower T d values were found with increasing concentrations. δH values of arachin were affected by urea. SDS affected δH values and thermal stability of conarachin; the arachin fraction showed higher resistance to SDS-induced denaturation. DTT addition did not affect conarachin stability, although enthalpy values decreased significantly. On the other hand, arachin was greatly affected by DTT. In summary, thermal denaturation parameters of PPI were sensitive to water content, indicating that polar groups of arachin and conarachin contribute to structure stabilization. Urea addition mainly affected the structure of the arachin fraction, which was attributed to its higher surface hydrophobicity. Results obtained from SDS and DTT suggest that hydrophobic interactions and disulfide bonds play an important role in structure maintenance of arachin and conarachin.